Effect of some environmental factors on the presence and density of the snail Melanoides tuberculata (Müller, 1774) in the tidal region of Shatt Al-Arab, Iraq Basrah - Al-Baghdadi, Nada M.; Sultan, Entesar N.; Abdullah, Abdul Aziz M. (Iraqi Journal of Aquaculture, 2023)
The current study was conducted on Melanoides tuberculate in three stations for the period from December 2017 to November 2018 (Al-Sharash, Al-Salhiya and Al-Dweab), as the samples were collected monthly. Some environmental factors were measured, such as the water temperature. The lowest water temperature was 12°C during January and the highest temperature was 33°C during July, both in Al-Salhiya station. The pH values ​​were between 7.5 in the three stations and 8.9 during July in Al-Sharash, and the lowest was recorded. The salinity value was 0.5‰ in April and November at Al-Sharash station, and the highest value was recorded at 39.3‰ during July for Al-Dweab station. The values ​​of the current speed ranged between 0.01)-95 (0.0 m/s in Al-Sharash and Al-Salhiya stations, respectively, while the values ​​of dissolved oxygen ranged between (12.1) -5.1) mg/liter during August and May in Al-Salhiya and Al-Sharash stations respectively, As for the bottom sediments, all the stations were alluvial with few and different proportions of sand and clay. The study also showed that the environmental factors have an impact on the distribution and spread of this species in the intertidal zone. It also found a significant direct relationship between density of M. tuberculata with dissolved oxygen and an inverse relationship with salinity in Al-Sharash station, while in Al-Salhiya station a direct relationship was recorded between the density of M. tuberculata and dissolved oxygen and an inverse relationship between the density of M. tuberculata with salinity.